A New Approach to Polymorphism in Molecular Crystals: Substrate‐Mediated Structures Revealed by Lattice Phonon Dynamics. Issue 28 (2nd September 2022) - Salzillo, Tommaso; Brillante, Aldo
Abstract: The issue of polymorphism in molecular crystals is discussed, taking into account the substrate‐mediated structures, that is, structures grown at the interface of different substrates. Bulk and thin films of a compound both share the potentiality to display different crystal forms. However, unlike bulk polymorphs, whose structures are determined by their different molecular packing, thin film structures depend very much on the molecular organization of the organic layers on the substrate, which may, or may not, lead to an ordered structure, depending on the nature of the interface and on the growth conditions. Based on large part in some of the authors' recent works, these thin film structures are classified as distorted bulk, substrate‐selected and substrate‐stabilized polymorphs, with some subtle differences which may yield a polymorph to belong not exclusively to a single one of these categories. Some experiments are then focused upon, involving charge transport at the interface, as well as how far the effect of the surface goes. Furthermore, the authors comment on how the surface‐mediated structures evolve to the single crystal phase in the cases of pentacene and α‐sexithiophene. Finally, the transition from a 3‐ to a 2D regime of growth is shortly discussed in terms of low‐dimensional disorder. Abstract : This review aims to extend the issue of polymorphism to the new crystal forms induced at the interface between the surface and an organized molecular layered structure. The method of low frequency Raman scattering complements well the structural findings from XRD techniques. Growth and dynamics in 2D and 3D regimes are also discussed.